A Systematic Review of Permeable Pavements and Their Unbound Material Properties in Comparison to Traditional Subbase Materials - Dansani Vasanthan Muttuvelu; Erik Kjems (Infrastructures, 2021)
This paper is a literature review focused on permeable pavements and especially the permeable subbase material. Run-off water from the surface is traditionally let through a drainage system, and the roads are kept dry. Due to climate changes, heavy precipitation and high-intensity rainfalls are putting pressure on the infrastructure. Traditionally, water in subbase materials reduces the resilient E-moduli and the lifespan of the pavement design. Studies show that increasing saturation reduces the bearing capacity of a traditional subbase material. Unbound materials with highly grained fines and high moisture content have higher tendency to show reduced resilient E-moduli. One study was found where the E-moduli of five different coarse grained aggregates used in permeable pavements were examined through a triaxial test. It was found that the E-moduli varied from 110–371 MPa. Other studies examining the E-moduli of permeable subbases based on moisture content were not found. However, this paper discusses different experiences regarding the bearing capacity of traditional vs. permeable subbase materials. It also covers a discussion and an analysis of missing research areas that needs to be investigated for further knowledge about the usage of permeable pavements in areas with a risk of flooding.